Effect of Contaminated Surface Water by Residents of Brick Kilns on Antioxidants and Lipid Profile of Rats - Al-Safi, Duaa R.M.; Al Aboudi , Zahraa N.K. (Newinera Publisher, 2025)
Antioxidants and lipid markers have gained significant attention in recent decades for their pivotal role in promoting overall health and well-being. On other hand, the improper disposal of industrial effluents has emerged as a major environmental challenge leading to contamination of water sources that subsequently impact public health. Estimation of the effect of contaminated water by the residents of brick kilns on the level of antioxidants (CAT, GPX, and SOD), lipid peroxidation MDA, and lipid profile (TC, HDL, LDL, and TG). A total of 30 surface water samples were collected from the areas near the brick kilns located in Al-Hai, Al-Kut, and Badra cities into labeled plastic containers. Then, overall 60 rats were divided equally into two groups; the 1st was given tap water (negative control), and the 2nd was given the contaminated water (experimental). After 75 days, blood was collected from all animals to obtain the sera that tested using the specific species quantitative enzyme-linked sorbent assay (ELISA) kits to measure the concentration of antioxidants, lipid peroxidation and lipid profile. In comparison to values of control group, results of antioxidants including CAT (5.419 ± 0.363 pg/ml), GPX (24.533 ± 1.317 IU/ml) and SOD (4.013 ± 0.479 U/ml) were reduced significantly; while significant increases were shown in results of lipid peroxidation MDA (187.333 ± 10.402 ng/ml), as well as in LDL (641.611 ± 54.809 ng/ml). However, insignificant variation between the values of experimental and control groups was seen in values of TC (3.528 ± 0.332 nmol/ml), HDL (36.283 ± 1.881 ng/ml), and TG (567.556 ± 72.724 ng/ml).